18. Phytochemistry and Antibacterial Activity Test of Ethanol Extracts of Soursop flower (Annona muricata L.) against Salmonella enteritidis - Zuraidawati Zuraidawati; Maryulia Dewi; Darmawi Darmawi; Sugito Sugito; Abdullah Hamzah; Winaruddin Winaruddin (Jurnal Medika Veterinaria, 2019)
The purpose of this research was to identified the compounds in ethanol extract of soursop flower and determined the antibacterial activity of the soursop flower extract on Salmonella enteritidis. The phytochemistry screening was done to identify the secondary metabolite compounds of this extract. The concentrations used of ethanol extract of soursop flower were 10%, 20%, 30%, 40%, 50%, with ampicillin 10 μg/disc as the positive control and 10% Dimethyl Sulfoxide (DMSO) as the negative control. The antibacterial activity test of soursop flower ethanol extract against Salmonella enteritidis was held in vitro using the paper disc diffusion method by measuring the diameter of the inhibition zone. The phytochemistry screening showed that the ethanol extract of soursop flower had secondary metabolites such as alkaloids, phenolic, and flavonoid. The result of the antibacterial activity test showed that there was no inhibition zone (bright zone) at various concentrations. So, it can be concluded that soursop flower ethanol extract (Annona muricata L.) contained the secondary metabolites such as alkaloids, phenolic, and flavonoid, and also this extract had no antibacterial activity against Salmonella enteritidis